2020
DOI: 10.3390/nano10081572
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Grafted on Graphene Oxide: Hybrid Nanofiller for Effective and Low-Cost Proton Exchange Membranes

Abstract: A nanostructured hybrid material consisting of TiO2 nanoparticles grown and stabilized on graphene oxide (GO) platelets, was synthesized and tested as nanofiller in a polymeric matrix of sulfonated polysulfone (sPSU) for the preparation of new and low-cost nanocomposite electrolytes for proton exchange membrane fuel cell (PEMFC) applications. GO-TiO2 hybrid material combines the nanoscale structure, large interfacial area, and mechanical features of a 2D, layered material, and the hygroscopicity properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…It also improved mass transfer, compared to a layer by layer rGO electrode, augmenting Pt dispersion and increasing oxidation resistance as well. Regarding the electrolyte membrane, Simari et al [ 85 ] synthesized a composite of TiO 2 @GO with sulfonated polysulfone as an alternative to the most common Nafion membrane, which may dehydrate easily reducing proton conductivity. The composite showed 22% higher water uptake and 5% higher ion exchange capacity, with the TiO 2 @GO hybrid limiting the degradation of sulfonic acid groups.…”
Section: Ceramic/graphene Composites Used In Energy Production and Storagementioning
confidence: 99%
“…It also improved mass transfer, compared to a layer by layer rGO electrode, augmenting Pt dispersion and increasing oxidation resistance as well. Regarding the electrolyte membrane, Simari et al [ 85 ] synthesized a composite of TiO 2 @GO with sulfonated polysulfone as an alternative to the most common Nafion membrane, which may dehydrate easily reducing proton conductivity. The composite showed 22% higher water uptake and 5% higher ion exchange capacity, with the TiO 2 @GO hybrid limiting the degradation of sulfonic acid groups.…”
Section: Ceramic/graphene Composites Used In Energy Production and Storagementioning
confidence: 99%
“…X-ray diffraction (XRD) measurements were performed using the Cu-Kα radiation of a Bruker Axis Diffractometer/Reflectometer (D8) equipped with a Dynamic Scintillation Detector, NaI, and with a Göbel mirror [ 61 ]. Spectra were collected at room temperature in the 2θ range from 5° to 40°, in steps of 0.03°, and the counting time was 1 s/step [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…For this study, LDH based on Mg 2+ /Al 3+ (2:1 metals ratio) with NO 3 − interlayer anion was chosen and membranes at 3 wt.% of filler loading with respect to the polymer were prepared by simple solution intercalation. According to the literature, 3 wt.% of loading has been demonstrated to be the optimal one in most of the nanocomposite systems and for various types of inorganic materials [ 45 , 46 , 47 , 48 , 49 ]. Additionally, during our previous works, we have demonstrated that the introduction of 3 wt.% of LDH material can ensure the maximum improvement in terms of transport properties, conductivity values, and mechanical properties either in the case of Nafion-based [ 50 ], sPEEK-based [ 51 ], and sPSU-based [ 46 ] composite membranes.…”
Section: Introductionmentioning
confidence: 99%
“…For each membrane, the dumping factor plot exhibits a single peak, which can be assigned to the α transition (T g ) of the ionic clusters of the polymer. While Nafion [36] exhibits a T g of ca. 120 • C, the α-transition for SPEEK is shifted at remarkably higher temperatures, i.e., above 200 • C. This indicates this polyaromatic polymer can definitively withstand higher operating temperatures with respect to the Nafion benchmark.…”
Section: Mechanical Propertiesmentioning
confidence: 99%